2019
DOI: 10.1097/md.0000000000016893
|View full text |Cite
|
Sign up to set email alerts
|

Rare concurrence of ectopic intrathyroidal parathyroid gland and papillary thyroid carcinoma within a thyroid lobe

Abstract: Rationale: The inferior parathyroid glands derive from the third branchial pouch and seldom ectopically migrate to thyroid grand, mediastinum, thymus. Ectopic intrathyroidal parathyroid grand (ETPG) is rare and it cannot be consistently detected by any imaging examinations. The unusual ETPG is easily resected during thyroidectomy, which might cause postoperative hypoparathyroidism. Auto-transplantation of even a parathyroid gland can restore parathyroid function to some extent. Until now, there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…This might be because normal ITP is asymptomatic and US is insensitive in detecting them, while abnormal ITP lesions are associated with hyperparathyroidism and can more easily be distinguished through imaging techniques and FNA [17] , [18] . Both Chen et al and Velimezis et al in their studies reported that ectopic ITP was not detected through US and was accidently found during postoperative histological examination of the other present thyroid lesion, reportedly PTC [15] , [16] . The case in the current study was diagnosed for PTC through FNA without any detection of an ITP on US, and patient laboratory results were in normal limits.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…This might be because normal ITP is asymptomatic and US is insensitive in detecting them, while abnormal ITP lesions are associated with hyperparathyroidism and can more easily be distinguished through imaging techniques and FNA [17] , [18] . Both Chen et al and Velimezis et al in their studies reported that ectopic ITP was not detected through US and was accidently found during postoperative histological examination of the other present thyroid lesion, reportedly PTC [15] , [16] . The case in the current study was diagnosed for PTC through FNA without any detection of an ITP on US, and patient laboratory results were in normal limits.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports of ITP have demonstrated that ITP is usually asymptomatic, and any symptom or clinical findings are linked to associated thyroidal lesion that might be present [15] , [16] . Chen and colleagues reported a 27-year-old asymptomatic female case of ectopic ITP and PTC with normal family and medical history [15] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from thyroid nodules, non-thyroidal tissues such as parathyroid, thymus, salivary gland, uncommon cysts, lymph node and metastasis can be completely embedded in the thyroid, and most of these ectopic nonthyroidal tissues appear as predominantly hypoechoic on US [1,8,9]. In the differential diagnosis of thyroid nodules, this wide spectrum of the lesions should be always considered.…”
Section: Discussionmentioning
confidence: 99%